Intellectuals of the GT7 of ANPEd: between the academic field and the intervention in the social world (1994-1999) (Práxis Educativa, 2015)
This paper aims to problematize the positions of intellectuals of the Grupo de Trabalho Educação de Crianças de 0 a 6 anos (GT7) (Working Group for the Education of Children from 0 to 6 years of age), and of the Associação Nacional de Pós-Graduação e Pesquisa em Educação (ANPEd) (National Association for Postgraduate studies and Research in Education), involved in elaborating and implanting the Referencial Curricular Nacional para a Educação Infantil (RCNEI) (National Curricular Guidelines on Children’s Education). This article is based on ANPEd’s collective view and on the book  Educação infantil pós-LDB: rumos e desafios (‘Post-LDB children’s education: direction and challenges’), as well as on the concepts of intellectual drawn by Pierre Bourdieu and Michel Foucault to sustain that the intellectuals of the GT7, in the name of autonomy in the academic field and scientific and specialized knowledge, adopted a critical posture towards the RCNEI when indicating the possibilities and mainly the limits of this policy presented by MEC.               Keywords: Intellectual History. Intellectuals. Children’s education.